Percutaneous management of paravalvular leaks. Issue 13 (22nd October 2021) - Giblett, Joel P; Williams, Lynne K; Moorjani, Narain; Calvert, Patrick A
Abstract : Paravalvular leak (PVL) is a challenging complication of valve replacement surgery that can cause heart failure and haemolysis. Surgical repair is the traditional treatment for severe, symptomatic PVL, but many patients with PVL fall into high-risk categories for redo surgery. Percutaneous techniques for closure of PVL have been increasingly refined over the last decade with availability of approved purpose-specific devices for closure. Percutaneous closure requires a heart team approach, with attention paid to appropriate preprocedural and periprocedural imaging to ensure a successful closure with minimal residual leak or complication. There are limited studies addressing the selection of a percutaneous approach to PVL. No randomised trials comparing surgical and percutaneous repair have been conducted. Large national registries from the UK and Ireland and from Spain have demonstrated that high rates of technical success can be achieved, with mortality comparable with surgical repair. Six retrospective studies comparing surgical and percutaneous approaches have been published. These broadly show comparable technical success between the interventions, with reduced short-term mortality among patients treated percutaneously. Long-term outcomes were similar between both treatment options. Percutaneous repair is an attractive treatment option in many patients due to its reduced invasiveness and quicker recovery period. However, more prospective studies are needed to validate its place in the armamentarium of the heart team.